Numerical methods for solving applied optimal control problems - Gornov, A. Yu; Tyatyushkin, A. I.; Finkelstein, E. A. (Computational mathematics and mathematical physics, 2013)
For an optimal control problem with state constraints, an iterative solution method is described based on reduction to a finite-dimensional problem, followed by applying a successive linearization algorithm with the use of an augmented Lagrangian. The efficiency of taking into account state constraints in optimal control computation is illustrated by numerically solving several application problems.